Chlamydomonas reinhardtii LFO1 Is an IsdG Family Heme Oxygenase - Lisa J. Lojek (American Society for Microbiology, 2017)
ABSTRACT Heme is essential for respiration across all domains of life. However, heme accumulation can lead to toxicity if cells are unable to either degrade or export heme or its toxic by-products. Under aerobic conditions, heme degradation is performed by heme oxygenases, enzymes which utilize oxygen to cleave the tetrapyrrole ring of heme. The HO-1 family of heme oxygenases has been identified in both bacterial and eukaryotic cells, whereas the IsdG family has thus far been described only in bacteria. We identified a hypothetical protein in the eukaryotic green alga Chlamydomonas reinhardtii, which encodes a protein containing an antibiotic biosynthesis monooxygenase (ABM) domain consistent with those associated with IsdG family members. This protein, which we have named LFO1, degrades heme, contains similarities in predicted secondary structures to IsdG family members, and retains the functionally conserved catalytic residues found in all IsdG family heme oxygenases. These data establish LFO1 as an IsdG family member and extend our knowledge of the distribution of IsdG family members beyond bacteria. To gain further insight into the distribution of the IsdG family, we used the LFO1 sequence to identify 866 IsdG family members, including representatives from all domains of life. These results indicate that the distribution of IsdG family heme oxygenases is more expansive than previously appreciated, underscoring the broad relevance of this enzyme family. IMPORTANCE This work establishes a protein in the freshwater alga Chlamydomonas reinhardtii as an IsdG family heme oxygenase. This protein, LFO1, exhibits predicted secondary structure and catalytic residues conserved in IsdG family members, in addition to a chloroplast localization sequence. Additionally, the catabolite that results from the degradation of heme by LFO1 is distinct from that of other heme degradation products. Using LFO1 as a seed, we performed phylogenetic analysis, revealing that the IsdG family is conserved in all domains of life. Additionally, C. reinhardtii contains two previously identified HO-1 family heme oxygenases, making C. reinhardtii the first organism shown to contain two families of heme oxygenases. These data indicate that C. reinhardtii may have unique mechanisms for regulating iron homeostasis within the chloroplast.